ADP-Ribosylation Factor-Interacting Protein 2 Acts as a Novel Regulator of Mitophagy and Autophagy in Podocytes in Diabetic Nephropathy - Haihua Guo; Manuel Rogg; Julia Keller; Ann-Kathrin Scherzinger; Julia Jäckel; Charlotte Meyer; Alena Sammarco; Martin Helmstädter; Oliver Gorka; Olaf Groß; Christoph Schell; Wibke Bechtel-Walz (MDPI AG, 2024)
(1) Background: Differentiated podocytes are particularly vulnerable to oxidative stress and cellular waste products. The disease-related loss of postmitotic podocytes is a direct indicator of renal disease progression and aging. Podocytes use highly specific regulated networks of autophagy and endocytosis that counteract the increasing number of damaged protein aggregates and help maintain cellular homeostasis. Here, we demonstrate that ARFIP2 is a regulator of autophagy and mitophagy in podocytes both in vitro and in vivo. (2) Methods: In a recent molecular regulatory network analysis of mouse glomeruli, we identified ADP-ribosylation factor-interacting protein 2 (Arfip2), a cytoskeletal regulator and cofactor of ATG9-mediated autophagosome formation, to be differentially expressed with age. We generated an Arfip2-deficient immortalized podocyte cell line using the CRISPR/Cas technique to investigate the significance of Arfip2 for renal homeostasis in vitro. For the in vivo analyses of Arfip2 deficiency, we used a mouse model of Streptozotozin-induced type I diabetes and investigated physiological data and (patho)histological (ultra)structural modifications. (3) Results: ARFIP2 deficiency in immortalized human podocytes impedes autophagy. Beyond this, ARFIP2 deficiency in human podocytes interferes with ATG9A trafficking and the PINK1-Parkin pathway, leading to the compromised fission of mitochondria and short-term increase in mitochondrial respiration and induction of mitophagy. In diabetic mice, Arfip2 deficiency deteriorates autophagy and leads to foot process effacement, histopathological changes, and early albuminuria. (4) Conclusions: In summary, we show that ARFIP2 is a novel regulator of autophagy and mitochondrial homeostasis in podocytes by facilitating ATG9A trafficking during PINK1/Parkin-regulated mitophagy.